(untitled) (translation. a transdisciplinary journal, 2022)
The media ecology approach to communication study proposes the analysis of the environments of communication-technological, historical, linguistic, psychological, and so on-in an attempt to better understand how sometimes hidden aspects of communication work together to affect the understanding, impact, and use of communication and communication products. As with any environment, the interaction of the elements offers new opportunities; an unstable or changing environment provides a particularly fruitful laboratory to understand communication. This essay applies the media ecology methodology to the translations project of the King James Version of the English Bible, first published in 1611 , during a tumultuous period of change in communication media and social relations.